An Improved Algorithm of Edge Detection for Aircraft Positioning - Dong, Lin-Lu; Xue, Zhi-Shuang; Zhao, Liang-Jun; Shi, Xiao-Shi (Journal of Vibration Testing and System Dynamics, 2026)
The method of aircraft positioning in the anti-UAV(unmanned aerial vehicle, UAV) system is detecting objects through an image. Its preprocessing process needs to extract the edge of the target aircraft, however, due to the influence of image acquisition technology and electromagnetic environment, the obtained aircraft image is often interfered by a lot of noise. The traditional edge detection algorithm and the method of using local uniform sparsity to enhance the features of the aircraft can not meet the engineering requirement of detecting the edge of the aircraft which has complex structure. Aiming at this problem, an algorithm of edge extraction for aircraft under strong noise is proposed. Firstly, searching high definition images of other aircrafts similar to the structure of the target aircraft in the database, the algorithm is used to learn the texture features of these images. Then, the missing texture features corrupted by strong noise are repaired, this process can achieve the goals of enhancing the target aircraft's detail features and weakening influence of the background's features. Finally, the edge of the target aircraft is successfully detected. The experimental results show that the proposed algorithm can effectively detect the edge of the aircraft under strong noise.